Strain Sensor with Enhanced Sensitivity for Wearable Electronics Using an Over‐Balanced Planar Elastomer. Issue 2 (14th February 2022) - Nie, Meng; Wen, Lei; Chen, Shuning; Ai, Lu; Shen, Jingcheng; Zhao, Yu‐na; Yin, Kuibo; Dou, Guangbin
Abstract : Front Cover : In article number 2100576 by Meng Nie, Guangbin Dou, and co‐workers, an over‐balanced planar elastomer inspired by auxetic structure is used as a new concept in producing novel wearable strain sensors, resulting gauge factors up to six times higher than those trialed from the typical sensors reported in the latest research.